NUMERICAL SIMULATION OF NONLINEAR SCHRODINGER EQUATION - Taylanov, Nizom; Urinov, Sunnatulla (Физико-технологического образование, 2022)
In this study the split-step Fourier method for the numerical simulation of the nonlinear Schrodinger equation. Approximate numerical solutions of the nonlinear Schrodinger equation are obtained by using Matlab software. It is shown that the proposed method improves the computational effort significantly. This improvement becomes more significant especially for large time evolutions. The applied here scheme can be used as an efficient tool in computational mathematics, namely in a class of nonlinear differential equations, which describe the theoretical quantum physics and engineering problems